ALTERNATIF PENGEMBANGAN RUANG PUBLIK KOTA: TAMAN SPOT BUDAYA DUKUH ATAS - JAKARTA - Gerry, Gerry; Fahmi, Erwin (Universitas Tarumanagara, 2021)
Since the end of the 1980s Indonesia’s property business has been growing rapidly, especially in Jakarta. The growth has transformed green open space gradually to commercial uses. Along with that, there has also been a social shift in Jakarta and its satellite cities. Citizen maximizes their earnings from working at the office and trading in order to maintain (and upgrade) their welfare. As a result, their leisure time (including enjoying the park) worn off. Taman Spot Budaya Dukuh Atas (TDA) has been a Jakarta provincial government’s solution to such issues, i.e decreasing number of parks and open spaces, and the limited time available to enjoy them. A review in user appreciation, adaptation to current and upcoming trends, and its compatibility as public space and third space will be a benchmark for modern public space development. This study applies a qualitative research approach with a case study method. TDA proves to be one of the people’s option to hang out at public space, especially in a crowded city district. TDA also fulfilled public space, third space, and Jakarta government’s goals. But better maintenance and improvement are needed to ensure its sustainability. The concept of public space that can be enjoyed in a short time are expected to be replicated to several other crowd points in Jakarta and other major cities in the future. Keywords: Dukuh Atas; green open space; user appreciation; modern public space AbstrakSejak akhir 1980-an bisnis properti berkembang pesat di Indonesia, khususnya di Jakarta. Perkembangan ini mengkonversi lahan-lahan terbuka hijau menjadi lahan dengan fungsi komersil. Seiring perkembangan tersebut, terjadi pula pergeseran sosial di Jakarta dan di kota-kota penyangganya. Masyarakat memaksimalkan perolehannya dari bekerja di kantor atau berdagang demi menjaga (dan meningkatkan) kesejahteraannya. Akibatnya, waktu luang untuk rekreasi (termasuk menikmati taman) menjadi berkurang. Taman Spot Budaya Dukuh Atas (TDA) adalah salah satu solusi Pemda DKI Jakarta dalam memberikan fasilitas ruang terbuka, sekaligus melayani kategori warga kota tersebut. Peninjauan apresiasi pengguna, adaptasi dengan kecenderungan yang ada, dan kesesuaiannya sebagai ruang publik serta ruang ketiga menjadi tolok ukur bagi alternatif pengembangan ruang publik modern. Penelitian ini menggunakan pendekatan penelitian kualitatif, dengan metode studi kasus. TDA dapat menjadi pilihan masyarakat untuk menikmati ruang publik, khususnya di pusat kota. TDA sendiri sudah memenuhi kriteria sebagai ruang publik dan ruang ketiga, serta sudah sesuai dengan tujuan awal Pemda DKI. Namun diperlukan pemeliharaan dan pengembangan dari pengelola taman yang lebih baik, agar ruang publik dapat berkelanjutan. Konsep penyediaan ruang publik yang dapat dinikmati secara singkat ini diharapkan dapat direplikasi di beberapa titik keramaian di Jakarta dan kota besar lainnya ke depan.